Post-chemotherapy changes in breast with evaluation of residual carcinoma burden - Tiwari, Kavita; Verma, Nidhi (Asian Journal of Medical Sciences, 2024)
Background: Neoadjuvant therapy (NAT) is an important tool for the treatment of patients with breast cancer. The aim of NAT is to make it operable for patients with locally advanced breast cancer, to shrink early-stage tumors – thus allowing for breast conservation. Pathological complete response achieved by post-chemotherapy is an independent factor in the long-term survival of patients. Thus, the histopathological components of post-chemotherapy changes such as cellularity and lymph node (LN) tumor deposits, when combined, help to assess residual carcinoma burden. Aims and Objectives: This study aims to analyze various histopathological changes in the breast after neoadjuvant chemotherapy with the objective of evaluating post-chemotherapy response and residual cancer burden. Materials and Methods: A total of 34 cases of post-chemotherapy modified radical mastectomy specimens were analyzed for pathological response (pCR) and residual cancer burden were evaluated. Tumor cellularity, stromal changes, lymphovascular invasion, and LN involvement were noted. Results: The age group of presentation of 34 cases ranged from 30 to 75 years of age with the mean age being 43.5 years. The most common histomorphological finding was fibrosis/elastosis and vacuolation with 26 (76.5%) and 24 (70.6%) cases, respectively. The number of cases that showed partial pCR was 30 (88.2%) and 1 (2.9%) case showed a pathological complete response which belonged to Stage 0, pathological no response was shown by 3 (8.8%) cases which belonged to Stage II and Stage IV. Conclusion: Post-chemotherapy response of neoadjuvant chemotherapy in breast carcinoma is important for prognosis and predictive information for disease relapse.